Experimental Study on Mechanical Properties and Acoustic Emission Characteristics of Water Bearing Sandstone under Stable Cyclic Loading and Unloading - Xinzhan Qin; Yu Zhou; Manchao He (Shock and Vibration)
Due to the adjustment of energy structure, a large number of coal mines are abandoned. Considering the environmental and economic effects, many experts proposed to use the abandoned mine cavern as the reservoir of the pumped storage power station. Furthermore, considering the long-term effects of repeated pumping and drainage and hydrodynamic pressure on the surrounding rock in coal mines, a large amount of sandstone was collected from the Ruineng coal mine in Yan’an city to carry out a series of laboratory tests. Through uniaxial compression testing of rock samples with different water content rates, combined with acoustic emission (AE) analysis, the strength softening and macrodeformation characteristics are obtained, and the influence of water content on acoustic emission characteristics is clarified. The mechanical properties of water bearing rock under cyclic loading and unloading experiments with varying upper limits are obtained using a triaxial test system, and the precursory information of rock failure is captured, providing significant guidance for stability analysis and instability warning for surrounding rock in pumped storage power stations.